District-level hospital trauma care audit filters: Delphi technique for defining context-appropriate indicators for quality improvement initiative evaluation in developing countries. Issue 1 (January 2016) - Stewart, Barclay T.; Gyedu, Adam; Quansah, Robert; Addo, Wilfred Larbi; Afoko, Akis; Agbenorku, Pius; Amponsah-Manu, Forster; Ankomah, James; Appiah-Denkyira, Ebenezer; Baffoe, Peter; Debrah, Sam; Donkor, Peter; et al.
Abstract: Introduction: Prospective clinical audit of trauma care improves outcomes for the injured in high-income countries (HICs). However, equivalent, context-appropriate audit filters for use in low- and middle-income country (LMIC) district-level hospitals have not been well established. We aimed to develop context-appropriate trauma care audit filters for district-level hospitals in Ghana, was well as other LMICs more broadly. Methods: Consensus on trauma care audit filters was built between twenty panellists using a Delphi technique with four anonymous, iterative surveys designed to elicit: (i) trauma care processes to be measured; (ii) important features of audit filters for the district-level hospital setting; and (iii) potentially useful filters. Filters were ranked on a scale from 0 to 10 (10 being very useful). Consensus was measured with average percent majority opinion (APMO) cut-off rate. Target consensus was defined a priori as: a median rank of ≥9 for each filter and an APMO cut-off rate of ≥0.8. Results: Panellists agreed on trauma care processes to target (e.g. triage, phases of trauma assessment, early referral if needed) and specific features of filters for district-level hospital use (e.g. simplicity, unassuming of resource capacity). APMO cut-off rate increased successively: Round 1 – 0.58; Round 2 – 0.66; Round 3 – 0.76; and Round 4 – 0.82. After Round 4, target consensus on 22 trauma care and referral-specific filters was reached. Example filters include: triage – vital signs are recorded within 15 min of arrival (must include breathing assessment, heart rate, blood pressure, oxygen saturation if available); circulation – a large bore IV was placed within 15 min of patient arrival; referral – if referral is activated, the referring clinician and receiving facility communicate by phone or radio prior to transfer. Conclusion: This study proposes trauma care audit filters appropriate for LMIC district-level hospitals. Given the successes of similar filters in HICs and obstetric care filters in LMICs, the collection and reporting of prospective trauma care audit filters may be an important step towards improving care for the injured at district-level hospitals in LMICs.